Book Reviews - Judy Halden-Sullivan; Karen Walker; Timothy Shea; Julie Nichols; Edward Sullivan (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Book Reviews Judy Halden-Sullivan - Making the Familiar Unfamiliar Karen Walker - Ritchhart, Ron, Mark Church, and Karin Morrison. Making Thinking Visible. San Francisco, CA: Jossey-Bass, 2011. Timothy Shea - Jobrack, Beverlee. Tyranny of the Textbook. New York: Rowman & Littlefield Publishers, Inc., 2012. Julie Nichols - FitzGerald, William. Spiritual Modalities: Prayer as Rhetoric and Performance. University Park, PA: Penn State Press, 2012. Edward Sullivan - Quesada, Donna. The Buddha in the Classroom: Zen Wisdom to Inspire Teachers. NY: Skyhorse Publishing, 2011.